Nitrogen transformation during composting: A comparison of cow manure and mixed cow and pig manure - Obsuwan, Kullanart; Phuekvilai, Prattana; Yookongkaew, Nimnara; Chaneam, Sumonmarn; Wanichacheva, Nantanit; Panishkan, Kamolchanok; Piachart, Pannipa; Artjinda, Piyakamol; Sanmanee, Natdhera (Science, Engineering and Health Studies, 2022)
Compost derived from manures is widely used and considered as a source of environmentally friendly nutrients to improve soil qualities. Two composts—cow manure compost and mixed cow and pig manure—were investigated for comparison. Forms of nitrogen—organic nitrogen (Org-N), ammonia nitrogen (NH4+), and nitrate nitrogen (NO3−)—and other physicochemical parameters were also studied. Results showed that composting increased total nitrogen and Org-N, and reduced organic matter. Nevertheless, the dynamics of NH4+ and NO3− differed between the composts. Cow compost has a higher nitrate fraction than a mixed compost throughout the study. This finding indicated mineralization via nitrification with low pH range between 6.59-6.88. In particular, the ammonification of mixed compost was greater than that of cow compost, especially during the thermophilic phase with the high pH range of 6.95–8.84. However, in the mature phase, the nitrification of mixed compost was greater and the amount of NO3− increased with time. The opposite trend was observed in cow compost. Therefore, adding pig manure may improve organic matters, particularly nitrogen input.